Medical Stress and Fear of Death and Dying in a Medical Patient Population. (November 2022) - Penberthy, Jennifer Kim; Russell, Genevieve; Phillips, Jackson; Banaji, Medhaa; Mann, Nicholas; Dameron, Elizabeth
We explored the relationship between medical illness-related stress and fear of death and dying in a population of individuals with self-reported medical illnesses. Medically ill participants identified their level of stress related to their medical condition, their level of fear of death and dying, and what treatments they would most prefer for addressing any fear of death and dying as well as their medical illness-related stress. Participants' medical illness-related stress levels were high with an average endorsed score of 7.23 out of 10 (most extreme stress). The majority (70%) of participants endorsed "some, " "a little, " or "no fear" of death and dying. Overall, reported medical illness-related stress was not significantly correlated with fear of death and dying. Seventy-five percent of participants reported preferring psychotherapy or mindfulness interventions for addressing their stress. Psychotherapy, anti-anxiety medications, and meditation were the top three choices for addressing fear of death and dying.